2023
DOI: 10.1021/jacsau.3c00319
|View full text |Cite
|
Sign up to set email alerts
|

Combining Atomic Layer Deposition with Surface Organometallic Chemistry to Enhance Atomic-Scale Interactions and Improve the Activity and Selectivity of Cu–Zn/SiO2 Catalysts for the Hydrogenation of CO2 to Methanol

Hui Zhou,
Scott R. Docherty,
Nat Phongprueksathat
et al.

Abstract: The direct synthesis of methanol via the hydrogenation of CO2, if performed efficiently and selectively, is potentially a powerful technology for CO2 mitigation. Here, we develop an active and selective Cu–Zn/SiO2 catalyst for the hydrogenation of CO2 by introducing copper and zinc onto dehydroxylated silica via surface organometallic chemistry and atomic layer deposition, respectively. At 230 °C and 25 bar, the optimized catalyst shows an intrinsic methanol formation rate of 4.3 g h–1 gCu –1 and selectivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Over the Cu–SiO 2 catalyst (Figure d), two bands at 2933 and 2854 cm –1 appeared within the first 10 min after the switch and stabilized. In agreement with previously reported assignments, we presume that these bands are associated with formate species adsorbed on the Cu 0 surface. Despite poor quality IR signal below 2000 cm –1 , a broad peak is visible around 1600 cm –1 (Figure S65), a characteristic ν­(C–O) band of the formate species .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Over the Cu–SiO 2 catalyst (Figure d), two bands at 2933 and 2854 cm –1 appeared within the first 10 min after the switch and stabilized. In agreement with previously reported assignments, we presume that these bands are associated with formate species adsorbed on the Cu 0 surface. Despite poor quality IR signal below 2000 cm –1 , a broad peak is visible around 1600 cm –1 (Figure S65), a characteristic ν­(C–O) band of the formate species .…”
Section: Resultssupporting
confidence: 93%
“…The absence of formate bands for more active Cu 0.93 Ga 0.07 –SiO 2 (Figure e) can be related to the accelerated hydrogenation (shorter lifetime or lower steady-state concentration) of the corresponding formate intermediate to methanol, due to the presence of promoter GaO x in the vicinity of Cu. The accelerated rate of methanol formation could instead result in two bands at 2959 and 2857 cm –1 ascribed to methoxy species adsorbed on silica, previously observed for silica-supported Pd–Ga, Ni–Ga, and Cu–Zn catalysts. These methoxy species also detected over Cu 0.93 Ga 0.07 –SiO 2 are not absorbed directly on the active bimetallic surface but on the neighboring Si–OH groups.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Herein, the bimetallic alloy model was constructed by substituting the copper atoms with other transition metal (TM) atoms (Au, Ni, Pd, Pt and Zn). The primary rationale for selecting TM atoms was based on a literature review, which identified Au–Cu, 4,36,37 Ni–Cu, 6,38,39 Pd–Cu, 7,40–42 Pt–Cu 43,44 and Zn–Cu 45–47 as extensively documented copper-based catalytic models. Choosing these models may help ensure that the combination of transition metals represented by Au, Ni, Pd, Pt and Zn demonstrates reliable catalytic activity when paired with copper.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[6][7][8][9][10] In catalyst preparation, ALD can be used to introduce active metals, promoters and other modifiers with tuneable coating thicknesses and penetration depths inside a porous particle. 5,[10][11][12][13][14][15][16][17] In order to achieve the desired reactant deposition result with different reactants and porous substrates, diffusion-reaction modelling can be used to design and optimize the ALD process. In the diffusion-reaction model, the particle geometry has an effect on the reactant transport inside the porous particle.…”
Section: Introductionmentioning
confidence: 99%